Oncologic outcomes for different axillary staging techniques in patients with nodal-positive breast cancer undergoing neoadjuvant systematic treatment: a cancer registry study - Pfob, André; Kokh, Daria B.; Surovtsova, Irina; Riedel, Fabian; Morakis, Philipp; Heil, Jörg (Annals of surgical oncology, 2024)
BACKGROUND: Targeted approaches such as targeted axillary dissection (TAD) or sentinel lymph node biopsy (SLNB) showed false-negative rates of < 10% compared with axillary lymph node dissection (ALND) in patients with nodal-positive breast cancer undergoing neoadjuvant systemic treatment (NAST). We aimed to evaluate real-world oncologic outcomes for different axillary staging techniques. - METHODS: We identified nodal-positive breast cancer patients undergoing NAST from 2016 to 2021 from the state cancer registry of Baden-Wuerttemberg, Germany. Invasive disease-free survival (iDFS) was assessed using Kaplan-Meier statistics and multivariate Cox regression models (adjusted for age, ypN stage, ypT stage, and tumor biologic subtype). - RESULTS: A total of 2698 patients with a median follow-up of 24.7 months were identified: 2204 underwent ALND, 460 underwent SLNB (255 with ≥ 3 sentinel lymph nodes [SLNs] removed, 205 with 1-2 SLNs removed), and 34 underwent TAD. iDFS 3 years after surgery was 69.7% (ALND), 76.6% (SLNB with ≥ 3 SLNs removed), 76.7% (SLNB with < 3 SLNs removed), and 78.7% (TAD). Multivariate Cox regression analysis showed no significant influence of different axillary staging techniques on iDFS (hazard ratio [HR] for SLNB with < 3 SLNs removed 0.96, 95% confidence interval [CI] 0.62-1.50; HR for SLNB with ≥ 3 SLNs removed 0.86, 95% CI 0.56-1.3; HR for TAD 0.23, 95% CI 0.03-1.64; ALND reference), and for ypN+ (HR 1.92, 95% CI 1.49-2.49), triple-negative breast cancer (HR 2.35, 95% CI 1.80-3.06), and ypT3-4 (HR 2.93, 95% CI 2.02-4.24). - CONCLUSION: These real-world data provide evidence that patient selection for de-escalated axillary surgery for patients with nodal-positive breast cancer undergoing NAST was successfully adopted and no early alarm signals of iDFS detriment were detected.